Estimativa de parâmetros genéticos para caracteres silviculturais e densidade do lenho em teste de progênies de Eucalyptus urophylla - Henriques, Eduardo Pinheiro [UNESP]; De Moraes, Cristiano Bueno; Sebbenn, Alexandre Magno; Filho, Mario Tomazello; De Moraes, Mário Luiz Teixeira [UNESP]; Mori, Edson Seizo [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2017)
In eucalypt species, progeny tests of open pollinated trees are usually used for selecting superior genotypes in genetic improvement programs. In this study, genetic parameters were estimated in a progeny test of Eucalyptus urophylla for the traits total tree height, diameter at breast height (DBH), stem volume and apparent density of the wood at 1, 2, 3, 5 and 7 years of age. The experimental design was randomized blocks with 77 treatments, 6 replicates and plots containing 5 plants in rows. The likelihood ratio test (LRT) revealed highly significant differences at a probability level of 1% (p<0.01) between the traits assessed, except for DBH and apparent density of the wood at the 1st year of growth, which were significant (p<0.05) and not significant, respectively. The values of the residual coefficients of variation were 9.23% for tree height, 10.66% for DBH, 29.74% for stem volume and 13.60% for wood density, all of them at the age of 1 year, decreasing according to the increase of age. The progeny mean heritabilities (h2m ) were 0.80 for tree height, 0.67 for DBH, 0.72 for stem volume and 0.83 for wood density, at age 7 years, when the rotation cycle is usually completed. The coefficients of determination of the plot effect of (C2p) were below 1% for all characters at the ages of 2, 3, 5 and 7 years. Accuracies (r'aa) were 87% for tree height, 78% for DBH, 83% for stem volume and 90% for wood density after the second year of growth for all traits and ages. The results indicate a strong genetic control for the traits associated to the tree growth and wood density, with the possibility of obtaining genetic gains when the selection is performed both within and among progenies.
Genetic parameters estimates for silvicultural traits and wood density in Eucalyptus urophylla progeny test
Keywords: Genetic parameters; Progeny test; Wood density; X-ray densitometry